Pemberdayaan Masyarakat Dalam Pengelolaan Pekerjaan Sebagai Upaya Peningkatan Sumber Daya Manusia Di Bendungan Desa Getas Gebyur - Alfina Arum Fawaida; Muhamad Rifa’i Subhi (Pakis Journal Institute, 2024)
The research results show that community empowerment in work management has a positive impact in increasing human resources. Empowerment program through training, mentoring and active community participation in decision making with knowledge, skills and community awareness with the aim of exploring and analyzing empowerment efforts in work management as a strategy to increase human resources. However, this management identified several challenges faced in implementing empowerment, including resources, conflicts of interest and resistance to change. This mentoring activity uses a qualitative approach with a case study approach. Community empowerment in managing work at the Getas Gebyur Wates Village Dam has great potential as a strategy to increase human resources. However, sustained and comprehensive efforts are needed to overcome challenges and maximize the benefits of empowerment efforts.